2012
DOI: 10.1097/bsd.0b013e318228bbed
|View full text |Cite
|
Sign up to set email alerts
|

Polymethylmethacrylate Augmentation of Pedicle Screws Increases the Initial Fixation in Osteoporotic Spine Patients

Abstract: Reinforcement of pedicle screws using PMMA augmentation may be a feasible surgical technique for osteoporotic spines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
93
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(96 citation statements)
references
References 0 publications
1
93
0
2
Order By: Relevance
“…Therefore, we used a cyclic loading protocol, because this seems to best approximate the clinical loading scenario. Preliminary clinical studies showed a decrease in implant loosening rates with cement augmentation in the osteoporotic proximal femur [20] and spine [38]. Cement augmentation of sacroiliac screw fixation has been reported in small case reports and series [41,46], and few complications were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we used a cyclic loading protocol, because this seems to best approximate the clinical loading scenario. Preliminary clinical studies showed a decrease in implant loosening rates with cement augmentation in the osteoporotic proximal femur [20] and spine [38]. Cement augmentation of sacroiliac screw fixation has been reported in small case reports and series [41,46], and few complications were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have demonstrated the effectiveness and success of this procedure in patients with primary spinal tumors, metastasis, trauma and infection [12][13][14][15][16]. Multiple anchor points distribute corrective forces over a greater number of segments associated with cemented screws minimize risk of loosening and pull out of conventional pedicle screw [17][18][19]. We noticed a previously non reported complication: a vertebral collapse in T12 without clinical relevance.…”
Section: Discussionmentioning
confidence: 81%
“…20,31 Among these approaches, the FPSs augmented by PMMA has achieved the highest fixation strength and best clinical outcomes 1,26 . However, disadvantages remain, such as bone-cement leakage, 3 exothermic damage, 19,28 and pulmonary embolism.…”
Section: 26mentioning
confidence: 99%